LEAN-PRODUCTION В СИСТЕМІ УПРАВЛІННЯ ПРОМИСЛОВИМ ПІДПРИЄМСТВОМ (International Journal of Innovative Technologies in Economy, 2018)
The advantages and principles of using the concept of Lean-production in industrial enterprises and the place of Lean-management in the overall management system are discussed in the article. Well-known principles of economical production are universal, but each organization is unique, therefore, its principles corresponding to the sphere of activity of a particular enterprise will be formed. The uniqueness of the principles is formed on the basis of creating a map of flows of values. Application of the principles and tools of Lean management at the enterprise will improve the overall management system without breaking the structure of the management model. The advantage of introducing cost effective production will be to obtain a client-centered result. For the effective implementation of the Lean concept, enterprises need to identify, educate their leaders, train them, form a team, motivate staff, and show a personal example of the benefits of using Lean tools.